Assessing Exercise-Induced Bronchoconstriction in Children; The Need for Testing - Lammers, Natasja; van Hoesel, Maaike H. T.; Kamphuis, Marije; Brusse-Keizer, Marjolein; van der Palen, Job; Visser, Reina; Thio, Boony J.; Driessen, Jean M. M. (Frontiers in Pediatrics, 2019)
Objective Exercise-induced bronchoconstriction (EIB) is a specific morbidity of childhood asthma and a sign of insufficient disease control. EIB is diagnosed and monitored based on lung function changes after a standardized exercise challenge test (ECT). In daily practice however, EIB is often evaluated with self-reported respiratory symptoms and spirometry. We aimed to study the capacity of pediatricians to predict EIB based on information routinely available during an outpatient clinic visit. Methods A clinical assessment was performed in 20 asthmatic children (mean age 11.6 years) from the outpatient clinic of the MST hospital from May 2015 to July 2015. During this assessment, video images were made. EIB was measured with a standardized ECT performed in cold, dry air. Twenty pediatricians (mean years of experience 14.4 years) each evaluated 5 children, providing 100 evaluations, and predicted EIB severity based on their medical history, physical examination and video images. EIB severity was predicted again after additionally providing baseline spirometry results. Results Nine children showed no EIB, 4 showed mild EIB, 2 showed moderate and 5 showed severe EIB. Based on clinical information and spirometry results, pediatricians detected EIB with a sensitivity of 84% (95% CI 72%-91%) and a specificity of 24% (95% CI 14%-39%).The agreement between predicted EIB severity classifications and the validated classifications after the ECT was slight (Kappa = 0.05 (95% CI 0.00-0.17)). This agreement still remained slight when baseline spirometry results were provided (Kappa = 0.19 (95% CI 0.06-0.32)). Conclusion Pediatricians’ prediction of EIB occurrence was sensitive, but poorly specific. The prediction of EIB severity was poor. Pediatricians should be aware of this in order to prevent misjudgment of EIB severity and disease control.